2022
DOI: 10.3390/photonics9120941
|View full text |Cite
|
Sign up to set email alerts
|

Security of Bennett–Brassard 1984 Quantum-Key Distribution under a Collective-Rotation Noise Channel

Abstract: The security analysis of the Ekert 1991 (E91), Bennett 1992 (B92), six-state protocol, Scarani–Acín–Ribordy–Gisin 2004 (SARG04) quantum key distribution (QKD) protocols, and their variants have been studied in the presence of collective-rotation noise channels. However, besides the Bennett–Brassard 1984 (BB84) being the first proposed, extensively studied, and essential protocol, its security proof under collective-rotation noise is still missing. Thus, we aim to close this gap in the literature. Consequently,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 63 publications
1
3
0
Order By: Relevance
“…The QBER comparison of BB84 and KMB09 under the channel noise effect is further illustrated in Table II. For an angle of π/4 we observe from Table II that the QBER obtained for our system model is similar to that obtained in [48] which uses BB84 QKD protocol over a similar type of noise channel model i.e. the collective-rotation noise channel.…”
Section: Simulation Results and Discussionsupporting
confidence: 77%
“…The QBER comparison of BB84 and KMB09 under the channel noise effect is further illustrated in Table II. For an angle of π/4 we observe from Table II that the QBER obtained for our system model is similar to that obtained in [48] which uses BB84 QKD protocol over a similar type of noise channel model i.e. the collective-rotation noise channel.…”
Section: Simulation Results and Discussionsupporting
confidence: 77%
“…Step 8: Subsequently, Bob i sends the sequence |S 3 k to Trent. Finally, Bob i sends the sequence |S 2 1 , |S 3 1 to Alice. The transmission process uses decoy photons to ensure secure communication.…”
Section: Itmentioning
confidence: 99%
“…In particular, after quantum electrodynamics was established, it was confirmed that photons are medium particles for the transmission of electromagnetic information. Photons are often used for quantum information transmission [1][2][3][4] because of their excellent properties of easy generation and manipulation and their ability to transmit over long distances through free-space or fiber channels [5]. Therefore, It is very important and meaningful to study various applications in electronic commerce based on quantum mechanics using photons as information carriers.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the role of photons in quantum communication is of great significance. Quantum communication includes various protocols and applications, such as quantum key distribution (QKD) [2][3][4][5][6][7][8][9][10][11][12], quantum secret sharing (QSS) [13][14][15], quantum key agreement (QKA) [16][17][18], quantum private query (QPQ) [19][20][21], quantum multi-party computation (QMC) [22][23][24][25][26], and so on.…”
Section: Introductionmentioning
confidence: 99%